Business Case for Integrated Reporting in the Ni gerian Oil and Gas Sector (Issues in Social and Environmental Accounting (ISEA), 2013)
The oil and gas sector is the mainstay of the Nigerian economy, accounting for over 95% of its revenue. The study therefore examines the business case for the adoption of Integrated Reporting in the sector. Secondary data were sourced from the annual reports and stand-alone sustainability reports of the six multinational companies operating in the Nigerian oil and gas sector. The results found that efforts to address environmental, social and governance reporting (ESG) were adhoc, short term and unrelated to the core activities of the corporations and as such were not integrated into their business strategies and model. Information on ESG was also duplicated over many medium in a haphazard and distorted form. The study therefore concluded that the introduction of integrated reporting will streamline performance reporting that is in line with international best practice in the sector